2019
DOI: 10.2967/jnumed.119.233809
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of PET Tracers for the Differentiation of Tumor Progression from Treatment-Related Changes in High-Grade Glioma: A Systematic Review and Metaanalysis

Abstract: Posttreatment high-grade gliomas are usually monitored with contrast-enhanced MRI, but its diagnostic accuracy is limited as it cannot adequately distinguish between true tumor progression and treatment-related changes. According to recent Response Assessment in Neuro-Oncology recommendations, PET overcomes this limitation. However, it is currently unknown which tracer yields the best results. Therefore, a systematic review and metaanalysis were performed to compare the diagnostic accuracy of the different PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 53 publications
7
43
1
Order By: Relevance
“…A meta-analysis from Kim et al. considering six studies on 18 F-FET PET (212 scans overall) in this clinical scenario found a pooled sensitivity and specificity of 89% (95% CI, 82–94%) and 88% (95% CI, 76–94%) ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 89%
“…A meta-analysis from Kim et al. considering six studies on 18 F-FET PET (212 scans overall) in this clinical scenario found a pooled sensitivity and specificity of 89% (95% CI, 82–94%) and 88% (95% CI, 76–94%) ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 89%
“…Positron emission tomography (PET) utilizing the amino acid tracers O-(2-18 Ffluoroethyl)-L-tyrosine ( 18 FET) or (S-11 C-methyl)-L-methionine ( 11 C-MET) can be utilized to differentiate viable glioma tissue from treatment-induced changes with high sensitivity and specificity (21). Uncontrolled studies suggest that 18 FET-PET may detect tumor progression during anti-angiogenic treatment earlier than MRI (20,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 18 F-FDG-PET is far from meeting the requirements of modern disease detection technology. 18 F-FDG is based on glucose, but most disease tissues contain a lot of glucose which interfere with accuracy (de Zwart et al 2020 ; Langen et al 2017 ; Lohmann et al 2019 ). Therefore, more and more fluorinated PET tracers are being developed.…”
Section: Applications Of Fluorinated Compoundsmentioning
confidence: 99%